2019
DOI: 10.1007/s11356-019-04455-0
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Investigating the nexus among environmental pollution, economic growth, energy use, and foreign direct investment in 6 selected sub-Saharan African countries

Abstract: This research seeks to enhance the current literature by exploring the nexus among environmental contamination, economic growth, energy use, and foreign direct investment in 6 selected sub-Saharan African nations for a time of 34 years (1980–2014). By applying panel unit root (CADF and CIPS, cross-sectional independence test), panel cointegration (Pedroni and Kao cointegration test, panel PP, panel ADF), Hausman poolability test, and an auto-regressive distributed lag procedure in view of the pooled mean group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(71 citation statements)
references
References 81 publications
12
59
0
Order By: Relevance
“…In terms of causality, Jahangir Alam et al (2012) and Halicioglu (2009) found evidence of short run causality running from energy consumption to carbon emissions. Also, the presence of long run causality running in the same direction was found by studies such as Zhang and Chang (2009), Soytas et al (2007), Menyah and Wolde-Rufael (2010), Omri (2012), and Ssali et al (2019). In the same vein, studies such as Mirza and Kanwal (2017) and Al-Mulali and Sab (2018) found bidirectional causality between energy consumption and carbon emissions.…”
Section: Survey Of Empirical Literaturesupporting
confidence: 63%
“…In terms of causality, Jahangir Alam et al (2012) and Halicioglu (2009) found evidence of short run causality running from energy consumption to carbon emissions. Also, the presence of long run causality running in the same direction was found by studies such as Zhang and Chang (2009), Soytas et al (2007), Menyah and Wolde-Rufael (2010), Omri (2012), and Ssali et al (2019). In the same vein, studies such as Mirza and Kanwal (2017) and Al-Mulali and Sab (2018) found bidirectional causality between energy consumption and carbon emissions.…”
Section: Survey Of Empirical Literaturesupporting
confidence: 63%
“…But Omri, Daly, Rault, & Chaibi (2015) for MENA countries, Begum, Sohag, Abdullah, & Jaafar (2015) for Malaysia, Ahmad et al, (2017) for Croatia, Charfeddine & Mrabet (2017) for MENA countries and Dong, Sun, & Dong (2018) for China and (Al-mulali, Saboori, & Ozturk, 2015) for Vietnam delivered empirical evidence to indicate that an upsurge in economic growth has the capability to rise consumption of energy and eventually exacerbates CO2 emissions. Henceforth, from the perspective of causal relationship between economic growth and carbon emissions by (Abdulrashid, 2016;Charfeddine & Mrabet, 2017) is bidirectional while for (Chandia, Gul, Aziz, Sarwar, & Zulfiqar, 2018;Uddin, Salahuddin, Alam, & Gow, 2017) is unidirectional moving from carbon emissions to economic growth for (Dong et al, 2018;Ssali, Du, Mensah, & Hongo, 2019) is also unidirectional but move from economic growth to carbon emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…after applying ADRL approach to analyze the time series data for the period of 1991-2015, Kouton and Amonle (2019) explore the influence of consuming renewable energy on economic growth in Cote d'Ivoire and the outcome revealed that the influence is mixed in the short-run while the it is insignificant in the long-run and that brings to a conclusion that energy consumption transition is on the process in the country. In discovering the relationship between environmental pollution, energy consumption, foreign direct investment and economic growth within the context of selected 6 sub-Saharan Africa covering the period of 1980 to 2014, Ssali, Du, Mensah, and Hongo (2019) applied panel cointegration and ARDL in view of the PMG revealed that bidirectional causality exist running from energy use to CO2 emissions in the short-run and long-run unidirectional causality also exists running from energy use to CO2 emissions and from CO2 to foreign direct investment all in the study periods in selected sub-Saharan Africa.…”
Section: Literature Reviewmentioning
confidence: 99%